2022
DOI: 10.3390/biology11030431
|View full text |Cite
|
Sign up to set email alerts
|

The VIP/VPAC1R Pathway Regulates Energy and Glucose Homeostasis by Modulating GLP-1, Glucagon, Leptin and PYY Levels in Mice

Abstract: Vasoactive Intestinal Peptide binds with high affinity to VPAC1R and VPAC2R, thus regulating key physiologic functions. Previously, we documented in VIP−/− mice a leaner body phenotype and altered metabolic hormones. Past reports described in VPAC2−/− mice impaired circadian rhythm, reduced food intake, and altered metabolism. To better define the effects of VPAC1R on body phenotype, energy/glucose homeostasis, and metabolism, we conducted a 12-week study in a VPAC1R null model. Our results reveal that VPAC1−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…This mechanism could be mediated through the VPAC2 receptor, as feeding behavior observations in VPAC2 −/− mice showed a significantly reduced daily amount of food intake [77]. Our group recently demonstrated, by indirect calorimetric analysis, no significant differences in food consumption and the amount of time spent feeding in VPAC1 −/− mice, even though there was an increase in the number of feeding bouts during the dark cycle [78]. Previously, other researchers showed that a long-term treatment with a VPAC1 agonist inhibited food intake over a 28-day experimental period [79].…”
Section: Vip Effects On Appetite Satiety and Circadian Rhythmmentioning
confidence: 85%
“…This mechanism could be mediated through the VPAC2 receptor, as feeding behavior observations in VPAC2 −/− mice showed a significantly reduced daily amount of food intake [77]. Our group recently demonstrated, by indirect calorimetric analysis, no significant differences in food consumption and the amount of time spent feeding in VPAC1 −/− mice, even though there was an increase in the number of feeding bouts during the dark cycle [78]. Previously, other researchers showed that a long-term treatment with a VPAC1 agonist inhibited food intake over a 28-day experimental period [79].…”
Section: Vip Effects On Appetite Satiety and Circadian Rhythmmentioning
confidence: 85%
“…Similarly, no significant relationship was detected between plasma GLP‐1 and insulin glycemia response, stress glycemia, or plasma epinephrine in Vipr2 −/− mice. Little is known about the role of VPAC2R in GLP‐1 hormone regulation, although VPAC1R and VIP‐deficient mouse phenotypes and PACAP receptor antagonism are associated with increased fasting and postprandial GLP‐1 levels 7,72,73 . PAC1R‐ and VIP‐deficient fed or fasted mice also exhibit hyperinsulinemia 14,74 .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the role of VPAC2R in GLP-1 hormone regulation, although VPAC1R and VIP-deficient mouse phenotypes and PACAP receptor antagonism are associated with increased fasting and postprandial GLP-1 levels. 7,72,73 PAC1R-and T A B L E 3 PCR transcripts in adrenal gland.…”
Section: Vipr2 Gene-deletion Altered Gene Expression Of Hypothalamic ...mentioning
confidence: 99%
“…Similarly, no significant relationship was detected between plasma GLP-1 and insulin glycemia response, stress glycemia or plasma epinephrine in Vipr2 -/- mice. Little is known about the role of VPAC2R in GLP-1 hormone regulation, although VPAC1R and VIP-deficient mouse phenotypes and PACAP receptor antagonism are characterized by increased fasting and postprandial GLP-1 levels [7,72,73]. PAC1R- and VIP-deficient fed or fasted mice also exhibit hyperinsulinemia [14,74].…”
Section: Discussionmentioning
confidence: 99%